At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's rationalize the denominator of each given expression step-by-step:
### (i) [tex]\(\frac{2}{\sqrt{3} - \sqrt{5}}\)[/tex]
To rationalize the denominator, we multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{2}{\sqrt{3} - \sqrt{5}} \times \frac{\sqrt{3} + \sqrt{5}}{\sqrt{3} + \sqrt{5}} = \frac{2 (\sqrt{3} + \sqrt{5})}{(\sqrt{3} - \sqrt{5}) (\sqrt{3} + \sqrt{5})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{3} - \sqrt{5})(\sqrt{3} + \sqrt{5}) = (\sqrt{3})^2 - (\sqrt{5})^2 = 3 - 5 = -2 \][/tex]
Thus, we have:
[tex]\[ \frac{2 (\sqrt{3} + \sqrt{5})}{-2} = - (\sqrt{3} + \sqrt{5}) \][/tex]
### (ii) [tex]\(\frac{\sqrt{3} + \sqrt{2}}{\sqrt{3} - \sqrt{2}}\)[/tex]
Similarly, we multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{\sqrt{3} + \sqrt{2}}{\sqrt{3} - \sqrt{2}} \times \frac{\sqrt{3} + \sqrt{2}}{\sqrt{3} + \sqrt{2}} = \frac{(\sqrt{3} + \sqrt{2})^2}{(\sqrt{3} - \sqrt{2})(\sqrt{3} + \sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{3} - \sqrt{2})(\sqrt{3} + \sqrt{2}) = (\sqrt{3})^2 - (\sqrt{2})^2 = 3 - 2 = 1 \][/tex]
The numerator simplifies as follows:
[tex]\[ (\sqrt{3} + \sqrt{2})^2 = 3 + 2 + 2\sqrt{6} = 5 + 2\sqrt{6} \][/tex]
Thus, we have:
[tex]\[ \frac{5 + 2\sqrt{6}}{1} = 5 + 2\sqrt{6} \][/tex]
### (iii) [tex]\(\frac{6}{\sqrt{5} + \sqrt{2}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{6}{\sqrt{5} + \sqrt{2}} \times \frac{\sqrt{5} - \sqrt{2}}{\sqrt{5} - \sqrt{2}} = \frac{6 (\sqrt{5} - \sqrt{2})}{(\sqrt{5} + \sqrt{2}) (\sqrt{5} - \sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{5} + \sqrt{2})(\sqrt{5} - \sqrt{2}) = (\sqrt{5})^2 - (\sqrt{2})^2 = 5 - 2 = 3 \][/tex]
Thus, we have:
[tex]\[ \frac{6 (\sqrt{5} - \sqrt{2})}{3} = 2 (\sqrt{5} - \sqrt{2}) = 2\sqrt{5} - 2\sqrt{2} \][/tex]
### (iv) [tex]\(\frac{1}{8 + 5\sqrt{2}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{1}{8 + 5\sqrt{2}} \times \frac{8 - 5\sqrt{2}}{8 - 5\sqrt{2}} = \frac{8 - 5\sqrt{2}}{(8 + 5\sqrt{2})(8 - 5\sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (8 + 5\sqrt{2})(8 - 5\sqrt{2}) = 8^2 - (5\sqrt{2})^2 = 64 - 25 \times 2 = 64 - 50 = 14 \][/tex]
Thus, we have:
[tex]\[ \frac{8 - 5\sqrt{2}}{14} = \frac{8}{14} - \frac{5\sqrt{2}}{14} = \frac{4}{7} - \frac{5\sqrt{2}}{14} \][/tex]
### (v) [tex]\(\frac{3 - 2\sqrt{2}}{3 + 2\sqrt{2}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{3 - 2\sqrt{2}}{3 + 2\sqrt{2}} \times \frac{3 - 2\sqrt{2}}{3 - 2\sqrt{2}} = \frac{(3 - 2\sqrt{2})^2}{(3 + 2\sqrt{2})(3 - 2\sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (3 + 2\sqrt{2})(3 - 2\sqrt{2}) = 3^2 - (2\sqrt{2})^2 = 9 - 8 = 1 \][/tex]
The numerator simplifies as follows:
[tex]\[ (3 - 2\sqrt{2})^2 = 3^2 - 2 \times 3 \times 2\sqrt{2} + (2\sqrt{2})^2 = 9 - 12\sqrt{2} + 8 = 17 - 12\sqrt{2} \][/tex]
Thus, we have:
[tex]\[ \frac{17 - 12\sqrt{2}}{1} = 17 - 12\sqrt{2} \][/tex]
### (vi) [tex]\(\frac{\sqrt{3} - 1}{\sqrt{3} + 1}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{\sqrt{3} - 1}{\sqrt{3} + 1} \times \frac{\sqrt{3} - 1}{\sqrt{3} - 1} = \frac{(\sqrt{3} - 1)^2}{(\sqrt{3} + 1)(\sqrt{3} - 1)} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{3} + 1)(\sqrt{3} - 1) = (\sqrt{3})^2 - 1^2 = 3 - 1 = 2 \][/tex]
The numerator simplifies as follows:
[tex]\[ (\sqrt{3} - 1)^2 = (\sqrt{3})^2 - 2\sqrt{3} + 1 = 3 - 2\sqrt{3} + 1 = 4 - 2\sqrt{3} \][/tex]
Thus, we have:
[tex]\[ \frac{4 - 2\sqrt{3}}{2} = 2 - \sqrt{3} \][/tex]
### (vii) [tex]\(\frac{4}{\sqrt{7} + \sqrt{3}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{4}{\sqrt{7} + \sqrt{3}} \times \frac{\sqrt{7} - \sqrt{3}}{\sqrt{7} - \sqrt{3}} = \frac{4 (\sqrt{7} - \sqrt{3})}{(\sqrt{7} + \sqrt{3})(\sqrt{7} - \sqrt{3})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{7} + \sqrt{3})(\sqrt{7} - \sqrt{3}) = (\sqrt{7})^2 - (\sqrt{3})^2 = 7 - 3 = 4 \][/tex]
Thus, we have:
[tex]\[ \frac{4 (\sqrt{7} - \sqrt{3})}{4} = \sqrt{7} - \sqrt{3} \][/tex]
### (viii) [tex]\(\frac{1}{5 + 3\sqrt{2}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{1}{5 + 3\sqrt{2}} \times \frac{5 - 3\sqrt{2}}{5 - 3\sqrt{2}} = \frac{5 - 3\sqrt{2}}{(5 + 3\sqrt{2})(5 - 3\sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (5 + 3\sqrt{2})(5 - 3\sqrt{2}) = 5^2 - (3\sqrt{2})^2 = 25 - 9 \times 2 = 25 - 18 = 7 \][/tex]
Thus, we have:
[tex]\[ \frac{5 - 3\sqrt{2}}{7} \][/tex]
This completes the detailed, step-by-step rationalization of the denominators for each given expression.
### (i) [tex]\(\frac{2}{\sqrt{3} - \sqrt{5}}\)[/tex]
To rationalize the denominator, we multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{2}{\sqrt{3} - \sqrt{5}} \times \frac{\sqrt{3} + \sqrt{5}}{\sqrt{3} + \sqrt{5}} = \frac{2 (\sqrt{3} + \sqrt{5})}{(\sqrt{3} - \sqrt{5}) (\sqrt{3} + \sqrt{5})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{3} - \sqrt{5})(\sqrt{3} + \sqrt{5}) = (\sqrt{3})^2 - (\sqrt{5})^2 = 3 - 5 = -2 \][/tex]
Thus, we have:
[tex]\[ \frac{2 (\sqrt{3} + \sqrt{5})}{-2} = - (\sqrt{3} + \sqrt{5}) \][/tex]
### (ii) [tex]\(\frac{\sqrt{3} + \sqrt{2}}{\sqrt{3} - \sqrt{2}}\)[/tex]
Similarly, we multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{\sqrt{3} + \sqrt{2}}{\sqrt{3} - \sqrt{2}} \times \frac{\sqrt{3} + \sqrt{2}}{\sqrt{3} + \sqrt{2}} = \frac{(\sqrt{3} + \sqrt{2})^2}{(\sqrt{3} - \sqrt{2})(\sqrt{3} + \sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{3} - \sqrt{2})(\sqrt{3} + \sqrt{2}) = (\sqrt{3})^2 - (\sqrt{2})^2 = 3 - 2 = 1 \][/tex]
The numerator simplifies as follows:
[tex]\[ (\sqrt{3} + \sqrt{2})^2 = 3 + 2 + 2\sqrt{6} = 5 + 2\sqrt{6} \][/tex]
Thus, we have:
[tex]\[ \frac{5 + 2\sqrt{6}}{1} = 5 + 2\sqrt{6} \][/tex]
### (iii) [tex]\(\frac{6}{\sqrt{5} + \sqrt{2}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{6}{\sqrt{5} + \sqrt{2}} \times \frac{\sqrt{5} - \sqrt{2}}{\sqrt{5} - \sqrt{2}} = \frac{6 (\sqrt{5} - \sqrt{2})}{(\sqrt{5} + \sqrt{2}) (\sqrt{5} - \sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{5} + \sqrt{2})(\sqrt{5} - \sqrt{2}) = (\sqrt{5})^2 - (\sqrt{2})^2 = 5 - 2 = 3 \][/tex]
Thus, we have:
[tex]\[ \frac{6 (\sqrt{5} - \sqrt{2})}{3} = 2 (\sqrt{5} - \sqrt{2}) = 2\sqrt{5} - 2\sqrt{2} \][/tex]
### (iv) [tex]\(\frac{1}{8 + 5\sqrt{2}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{1}{8 + 5\sqrt{2}} \times \frac{8 - 5\sqrt{2}}{8 - 5\sqrt{2}} = \frac{8 - 5\sqrt{2}}{(8 + 5\sqrt{2})(8 - 5\sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (8 + 5\sqrt{2})(8 - 5\sqrt{2}) = 8^2 - (5\sqrt{2})^2 = 64 - 25 \times 2 = 64 - 50 = 14 \][/tex]
Thus, we have:
[tex]\[ \frac{8 - 5\sqrt{2}}{14} = \frac{8}{14} - \frac{5\sqrt{2}}{14} = \frac{4}{7} - \frac{5\sqrt{2}}{14} \][/tex]
### (v) [tex]\(\frac{3 - 2\sqrt{2}}{3 + 2\sqrt{2}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{3 - 2\sqrt{2}}{3 + 2\sqrt{2}} \times \frac{3 - 2\sqrt{2}}{3 - 2\sqrt{2}} = \frac{(3 - 2\sqrt{2})^2}{(3 + 2\sqrt{2})(3 - 2\sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (3 + 2\sqrt{2})(3 - 2\sqrt{2}) = 3^2 - (2\sqrt{2})^2 = 9 - 8 = 1 \][/tex]
The numerator simplifies as follows:
[tex]\[ (3 - 2\sqrt{2})^2 = 3^2 - 2 \times 3 \times 2\sqrt{2} + (2\sqrt{2})^2 = 9 - 12\sqrt{2} + 8 = 17 - 12\sqrt{2} \][/tex]
Thus, we have:
[tex]\[ \frac{17 - 12\sqrt{2}}{1} = 17 - 12\sqrt{2} \][/tex]
### (vi) [tex]\(\frac{\sqrt{3} - 1}{\sqrt{3} + 1}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{\sqrt{3} - 1}{\sqrt{3} + 1} \times \frac{\sqrt{3} - 1}{\sqrt{3} - 1} = \frac{(\sqrt{3} - 1)^2}{(\sqrt{3} + 1)(\sqrt{3} - 1)} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{3} + 1)(\sqrt{3} - 1) = (\sqrt{3})^2 - 1^2 = 3 - 1 = 2 \][/tex]
The numerator simplifies as follows:
[tex]\[ (\sqrt{3} - 1)^2 = (\sqrt{3})^2 - 2\sqrt{3} + 1 = 3 - 2\sqrt{3} + 1 = 4 - 2\sqrt{3} \][/tex]
Thus, we have:
[tex]\[ \frac{4 - 2\sqrt{3}}{2} = 2 - \sqrt{3} \][/tex]
### (vii) [tex]\(\frac{4}{\sqrt{7} + \sqrt{3}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{4}{\sqrt{7} + \sqrt{3}} \times \frac{\sqrt{7} - \sqrt{3}}{\sqrt{7} - \sqrt{3}} = \frac{4 (\sqrt{7} - \sqrt{3})}{(\sqrt{7} + \sqrt{3})(\sqrt{7} - \sqrt{3})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (\sqrt{7} + \sqrt{3})(\sqrt{7} - \sqrt{3}) = (\sqrt{7})^2 - (\sqrt{3})^2 = 7 - 3 = 4 \][/tex]
Thus, we have:
[tex]\[ \frac{4 (\sqrt{7} - \sqrt{3})}{4} = \sqrt{7} - \sqrt{3} \][/tex]
### (viii) [tex]\(\frac{1}{5 + 3\sqrt{2}}\)[/tex]
We multiply the numerator and the denominator by the conjugate of the denominator:
[tex]\[ \frac{1}{5 + 3\sqrt{2}} \times \frac{5 - 3\sqrt{2}}{5 - 3\sqrt{2}} = \frac{5 - 3\sqrt{2}}{(5 + 3\sqrt{2})(5 - 3\sqrt{2})} \][/tex]
The denominator simplifies as follows:
[tex]\[ (5 + 3\sqrt{2})(5 - 3\sqrt{2}) = 5^2 - (3\sqrt{2})^2 = 25 - 9 \times 2 = 25 - 18 = 7 \][/tex]
Thus, we have:
[tex]\[ \frac{5 - 3\sqrt{2}}{7} \][/tex]
This completes the detailed, step-by-step rationalization of the denominators for each given expression.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.